2020
DOI: 10.1002/cjp2.182
|View full text |Cite
|
Sign up to set email alerts
|

Expression of invadopodia markers can identify oral lesions with a high risk of malignant transformation

Abstract: Oral squamous cell carcinoma (OSCC) is the most common malignant tumor of the oral cavity and is usually preceded by a range of premalignant tissue abnormalities termed oral potentially malignant disorders. Identifying malignant transformation is critical for early treatment and consequently improved survival and decreased morbidity. Invadopodia (INV) are specialized subcellular structures required for cancer cell invasion. We developed a new method to visualize INV in keratinocytes using fluorescent immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 57 publications
0
19
0
1
Order By: Relevance
“…Indeed, invadopodia is present not only in established SCC, but its expression is also seen in premalignant nondysplastic and dysplastic lesions. Ali et al showed that progressing premalignant lesions that evolved to SCC have higher invadopodia scores, which were based on invadopodia markers, than non-progressing lesions [ 41 ]. This finding places invadopodia as an important marker for predicting malignant transformation and a potential determinant of treatment, where high-risk cases could require further aggressive treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, invadopodia is present not only in established SCC, but its expression is also seen in premalignant nondysplastic and dysplastic lesions. Ali et al showed that progressing premalignant lesions that evolved to SCC have higher invadopodia scores, which were based on invadopodia markers, than non-progressing lesions [ 41 ]. This finding places invadopodia as an important marker for predicting malignant transformation and a potential determinant of treatment, where high-risk cases could require further aggressive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A TNF-driven oral inflammation promotes a pro-inflammatory environment and proinvasion phenotype leading to the recruitment and activation of inflammatory cells and invadopodia formation [ 42 ]. An increase in local neutrophil infiltration is seen in aggressive cases with decreased survival rate [ 42 ] and also in progressing cases that undergo malignant transformation [ 41 ]. The identification of invadopodia promotors and regulators are quite important and can be a target for specific drugs development and anticancer therapy [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ten images were acquired from multiple regions of each tissue section using the SP8 confocal microscope (Leica) for human samples and the Quorum Spinning Disk confocal microscope (Quorum Technologies Inc.) for mouse specimens. Data analysis was performed using Volocity Image Analysis Software (PerkinElmer) using a custom protocol that detected positive expression based on fluorescent intensity and area for both human and mouse specimens ( 26 ). Identification of morphological features within each tissue section was accomplished using DAPI.…”
Section: Methodsmentioning
confidence: 99%
“…The invadepodia were defined as the yellow spot of MMP14, a marker of invadopodium [19], co-locating with F-actin.…”
Section: Immunofluorescence Analysismentioning
confidence: 99%